(untitled) (Medicine Today, 2025)
Introduction: Effect of fasting on human cognition has been a topic of recent research. The results of those studies are contradictory at best. Moreover, fasting as a religious ritual for an entire holy month of Ramadan has many denominators that differs from other pattern of fasting. Data on cognitive functions of physicians during Ramadan is scarce. We had investigated the effect of Ramadan fasting on physicians who are actively engaged in treating patients. Materials and Methods: This was a cross-sectional study conducted on 53 doctors working in a teaching hospital. Basic and task specific data were collected 1 week before and during Ramadan. On each occasion, cognition of each participant was tested using Trail making Test (TMT) part A and B, Simple reaction time (SRT) and Stroop test. Independent and paired t-test and multiple regression analysis were used for statistical analysis of Data in SPSS with significance level set at 0.05 or lower. Result: Overall, Ramadan fasting had no significant impact on cognitive capabilities of the physicians. Female participants (67.9%) performed better in TMT A and B and increased age was related to poorer results in SRT, TMT A and B. Higher diastolic blood pressure was associated with higher TMT B score. Neither sleep nor the blood glucose had any significant impact on cognition during Ramadan. Conclusion: In our study we had found no impairment of cognitive functions of treating physicians from different age group and specialties due the religious fasting on the holy month of Ramadan. Medicine Today 2025, Vol.37 (2): 237-240